The Tremendous Oath: Cosmological Horizons and the Hermeneutics of Stellar Positions (Sūrat Al-Wāqiʿah 56:75–76) - Umar Iqbal Butt (Penerbit Hellow Pustaka, 2026)
The Qurʾān frequently employs oaths involving celestial phenomena to underscore the veracity of Revelation. However, the oath found in the closing passages of Sūrat al-Wāqiʿah (56:75–76) distinguishes itself through unique syntactic negation and a specific focus on the